PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL PhET SIMULATION TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Rindiani, Rindiani; Yusmin, Edy; Fitriawan, Dona (Jurnal AlphaEuclidEdu, 2025)
Students need to have the ability to represent mathematically so that they can solve math problems using various representations. This study's goals to ascertain how using digital learning resources, particularly PhET simulations, affects junior high school students' mathematical representation abilities with relation to linear equations in one variable. This research involves 61 students from two classes and uses a quasi-experimental design. For sample selection, the cluster random sampling method was used. Test questions served as instruments with indicators of mathematical representation skills. With significance value < 0.001, The results of the independent sample t-test showed that there was a significant difference between the two groups. It was also obtained an effect size value of 1.45 with a very large category, Consequently, One may argue that when students study one-variable linear equations, employing PhET Simulation enhances their ability to represent mathematical ideas.